Physicians’ Knowledge, Altitudes, and Perceived Barriers of Inappropriate Prescribing for Older Patients in Shanghai, China - Yuan, Jing; Yin, Guizhi; Gu, Meng; Lu, Kevin Z.; Jiang, Bin; Li, Minghui (Frontiers in Pharmacology, 2022)
Background: Inappropriate medication use is common around the world, particularly among older patients, and, despite potentially being preventable, often leads to adverse clinical and economic outcomes. However, there is a dearth of information regarding this prominent issue in China. Objectives: To evaluate the extent to which the physician can correctly identify potentially inappropriate medication (PIM) in older patients and to understand physicians' attitudes towards improving PIM knowledge. Methods: An online, cross-sectional survey was conducted anonymously among practicing physicians in China from November through December 2020. Knowledge of PIM was accessed using seven clinical vignettes covering a wide variety of therapeutic areas. Source of information and perceived barriers regarding PIM were also evaluated. We performed the ordinary least square regression analysis to understand the potential factors related to physicians’ knowledge of PIM. Results: A total of 597 study participants were included in the analysis. More than half of them had never heard of any screening tool for PIMs (n=328, 54.9%) and the most frequently acknowledged tool was the China PIM Criteria (n=259, 43.4%). For the seven clinical vignettes testing physicians’ knowledge on the medications that should be generally avoided in older patients, the mean score was 2.91 points out of 7 (SD: 1.32), with the median score of 3 points (IQR: 2-4). Only one-third of the respondents were feeling confident when prescribing for older patients (n=255, 35.08%). Package inserts have been used as the major source of PIM information (always, n=177, 29.65%; frequently, n=286, 47.91%). Perceived barriers to appropriate prescribing include polypharmacy (n=460, 77.05%), lack of formal education on prescribing for the older patients (n=428, 71.69%). Conclusions: In this online survey evaluating physicians’ ability to detect PIM for older patients, approximately 40% of PIM were recognized, suggesting an insufficient level of knowledge about appropriate prescribing.